Helicobacter pylori is killed by nitrite under acidic conditions. Issue 3 (1st March 1998) - Dykhuizen, R S; Fraser, A; McKenzie, H; Golden, M; Leifert, C; Benjamin, N
Abstract : Background— Due to the expression of urease, Helicobacter pylori is able to establish itself in the human stomach under acidic conditions. A novel host defence mechanism was recently proposed, suggesting that the formation of salivary nitrite in symbiosis with facultative anaerobic bacteria in the oropharynx, is aimed at enhancing the antimicrobial activity of gastric juice. Aims— To investigate whether the addition of nitrite in physiological concentrations influences the resistance of H pylori to acid. Methods — H pylori cultured from fresh gastric biopsy specimens was exposed for 30 minutes to normal saline and to HCl/KCl buffer (0.2M) at pH 2 with urea (5 mM) added. The influence of potassium nitrite (50–1000 μmol/l) on bacterial survival was determined. Results— Addition of nitrite (1 mM) to acidic solutions (pH 2) resulted in complete kill of H pylori within 30 minutes exposure time whereas acid alone allowed the organism to survive (p<0.001). The antimicrobial effect of nitrite at pH 2 against H pylori was dose dependent and complete kill of organisms occurred at concentrations ⩾500 μmol/l. Conclusion— Acidified nitrite has antibacterial activity against H pylori . This should prompt further research into the effect of salivary nitrite on the survival of H pylori in the human stomach.